2018
DOI: 10.7717/peerj.5215
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations in the retinal pigment epithelium and photoreceptors of a Stargardt patient and three Stargardt mouse models: indication for the central role of RPE melanin in oxidative stress

Abstract: BackgroundStargardt disease (SD) is characterized by the accumulation of the age-pigment lipofuscin in the retinal pigment epithelium (RPE) and subsequent neuroretinal degeneration. The disease leads to vision loss early in life. Here, we investigate age-dependent ultrastructural changes in three SD mouse models: albino Abca4-/- and pigmented Abca4-/- and Abca4-/-.Rdh8-/- mice. Since we found indications for oxidative stress primarily in albino SD mice, we tested RPE melanin for its antioxidative capabilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 74 publications
9
70
0
Order By: Relevance
“…In rodents, RPE cells in the central retina contain a higher level of lipofuscin and a lower level of melanin than in the peripheral retina . The RPE degeneration induced by blue light was mainly located in the central area of eyes in pigmented Abca4 −/− mice, consistent with the spatial distribution of phototoxic RPE lipofuscin and RPE melanin that is known to have antioxidative properties . Based on our research, we conclude that lipofuscin accumulated in the RPE is the main mediator of photodamage in Abca4 −/− mice.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In rodents, RPE cells in the central retina contain a higher level of lipofuscin and a lower level of melanin than in the peripheral retina . The RPE degeneration induced by blue light was mainly located in the central area of eyes in pigmented Abca4 −/− mice, consistent with the spatial distribution of phototoxic RPE lipofuscin and RPE melanin that is known to have antioxidative properties . Based on our research, we conclude that lipofuscin accumulated in the RPE is the main mediator of photodamage in Abca4 −/− mice.…”
Section: Discussionsupporting
confidence: 78%
“…The peri-macular tissue from a 72-year-old patient with late-stage STGD1-like phenotype was investigated for ex vivo retinal AF. RPE cells of the peri-macular tissue were packed with pigment granules, including lipofuscin and melanolipofuscin stained by toluidine blue but devoid of melanosomes ( Figure 6D), as previously shown by Taubitz et al 24 Figure 6E,F show hyper lipofuscin-AF and hyper NIR-AF of pigment granules in RPE cells, respectively. The overlay yellow color in the merged fluorescence image demonstrated that most pigment granules were hyperautofluorescent at both excitation wavelengths (white arrows).…”
Section: Ex Vivo Retinal Af In Pigmented Abca4 −/− Mice After Bli Asupporting
confidence: 84%
See 3 more Smart Citations